PENGEMBANGAN KOMIK KIMIA BERBASIS INKUIRI PADA MATERI TATA NAMA SENYAWA KIMIA - Setya Wardani, Yulia Wahyu; Melati, Husna Amalya; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to produce chemistry comic that was feasible to be used. The form of the research was research and development (R & D) which is adopted from development of Sugiyono’s model for the research and development of Kemp’s model for set of equipment. Chemistry comic was validated by expert judgement to find out feasibilities. The feasibilities of the product were determined by expert judgement using validation sheets. The feasibilities of the product are consist of a feasibility of assessment sheet on the subject or content, feasibility of presentment, feasibility of language, feasibility of graph and feasibility of medium. The results showed that chemistry comic have a very feasible on the feasibility of content, presentment, language, graph, and medium with a total score 3.7; 3.8; 3.8; 3.7 and 3.7 respectively. Thus, chemistry comic can be used as supporting teaching material in the learning process at school or outside school. Keywords: chemistry comic, inquiry, feasibility of the product